TOGO PERFOMANCE IN RIVER AND PONDS AT CEMARA LABAT VILLAGE, CENTRAL KALIMANTAN - Febrina Berlianti; Roza Yusfiandayani; M. Fedi A. Sondita; Bambang Murdiyanto (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
Togo is a passive gear and classified as a trap and guiding barrier. Togo fishery in Cemara Labat village covers fishing activities in river and ponds. Penaeus indicus fishing in ponds are considered more profitable because catches obtained were greater thanboth in term of abundance and biomass. This study aims to identify fishing unit, compare the productivity and analyze differences in the number and size of catches of togo in river and ponds. The research used case study, survey and interview techniques to collect data on the performance of the fishing gear, productivity, the number and size of catches were analyzed using technical analysis, productivity trip and unpaired comparisson t-test. Results showed fishing unit of togo in river consists of fishing gear and boat, while the components on the fishing unit of togo in ponds consisting of fishing gear, ponds and hut. The t -test showed that it differed in abundance and biomass of shrimp on the different togo (p<0.05). The average size in river was 7879 cm with average catch was 10.60 kg while catches per trip was 31.47 kg trip-1 less than togo in ponds which reached 53.45 kg trip-1 with an average number and size where each 31.47 kg and 10.07 cm.